Turner syndrome with pulmonary arteriovenous malformation: a case report - Guo, Huibin; Chen, Hongqiao; Chen, Sihao; Tang, Shilong (Frontiers in Cardiovascular Medicine, 2025)
Turner syndrome (TS) is the most common sex chromosome abnormality disorder, caused by complete or partial absence of the X chromosome, its clinical manifestations primarily include short stature, gonadal dysgenesis, and characteristic cardiovascular malformations, pediatric cardiologists pay particular attention to coarctation of the aorta (CoA), which occurs in 15%–30% of TS patients and represents a life-threatening condition requiring prioritized screening during the neonatal and childhood periods (1– 3). Furthermore, due to lymphatic system developmental abnormalities, TS patients also face elevated risks of aortic root dilation, bicuspid aortic valve, and vascular structural anomalies (3). Pulmonary arteriovenous malformation (PAVM) is a rare pulmonary vascular anomaly, with an estimated prevalence of approximately 1 in 50,000 in the general population (1–3). Although the exact prevalence of PAVM in TS patients remains unclear, case series suggest a significantly elevated risk compared to the general population (estimated risk ratio: 5- to 10-fold), this association may be attributed to defective vascular elastic fiber development and dysregulated angiogenic signaling pathways in TS patients (4, 5). Here, we report the first documented case of TS complicated by PAVM, aiming to enhance clinicians' awareness of this rare comorbidity and provide evidence-based diagnostic and therapeutic recommendations.